Bevel Modification Effect on Rectangular Patch for UWB Using Theory Characteristics Mode - Liya Yusrina Sabila; Denti Agustina Damayanti (Universitas Ahmad Dahlan, 2022)
Ultra-wideband (UWB) is a communications technology that operates on frequencies between 3.1 and 10.6 GHz and has a wide bandwidth. This paper aims to look at the radiation characteristics of the structure using the Theory Characteristic Mode on a rectangular antenna with bevel modifications at the end of the patch. It can be seen from the active mode at the appropriate frequency to validate the antenna performance results. It was found that the proposed antenna has four operational modes in the antenna design before modification and seven active modes in the antenna design after modification. The antenna is made of FR-4 material with a thickness of 1.575 mm and a dielectric constant of 4.3. The bandwidth in the error measurement is around 7 GHz and a frequency range of 3.18 - 10.915 GHz with an S11 value of less than -10 and a VSWR value of less than 2. Ultra-wideband (UWB) adalah teknologi komunikasi yang beroperasi pada frekuensi antara 3,1 dan 10,6 GHz dan memiliki bandwidth yang sangat lebar. Makalah ini bertujuan untuk melihat karakteristik struktur radiasi menggunakan Theory Characteristic Mode pada antena rectangular dengan modifikasi bevel diujung patch. Untuk validasi hasil performansi antena dapat dilihat dari mode aktif pada frekuensi yang sesuai. Ditemukan bahwa antena yang diusulkan memiliki 4 mode aktif pada desain antena sebelum modifikasi dan 7 mode aktif pada desain antena sesudah modifikasi.. Antena terbuat dari bahan FR-4 dengan ketebalan 1,575 mm dan konstanta dielektrik 4,3. Bandwidth yang dicapai pada pengukuran adalah disekitar 7 GHz dan rentang frekuensi 3,18 - 10,915 GHz dengan nilai S11 kurang dari -10 dan nilai VSWR kurang dari 2.